PELATIHAN PEMBUATAN BONEKA PUPPET TEMA PROFESI SEBAGAI MEDIA PEMBELAJARAN ANAK USIA DINI DI TKN CIMENYAN KABUPATEN BANDUNG - Fitra, Annisa; Handayani, Wuri (Jurusan Seni Rupa ISBI Bandung, 2022)
This community service leads to the development of learning media for early childhood teachers (4 to 6 years). This service is located at TKN Cimenyan, Bandung Regency, West Java. The target of the training participants includes the teaching staff of TKN Cimenyan, learning media that will be developed through the use or manufacture of puppets from patchwork applications that have never been developed at TKN Cimenyan schools. Through this training, it is hoped that it can add insight to the teachers regarding Early Childhood learning media and to increase the creativity of early childhood. This training activity was carried out in several stages, including: the initial stage or data collection regarding the situation of the Cimenyan TKN school, the state of the school and the condition of the learning media of the students in Cimenyan TKN. Furthermore, the proposing team conducted a seminar as a form of introducing puppets and patchwork and workshops or training with the target that the Cimenyan TKN teachers were able to produce new learning media, and contribute to the multiplication and development of the use of patchwork with the aim of reducing cloth waste.Keywords: puppet dolls, patchwork, learning media, early childhood———————————————————————————-Pengabdian kepada masyarakat ini mengarah kepada pengembangan media pembelajaran bagi tenaga pengajar anak usia dini (4 sd 6 tahun). Pengabdian ini berlokasi di TKN Cimenyan Kabupaten Bandung Jawa Barat. Target peserta pelatihan mencakup para tenaga pengajar TKN Cimenyan, Media pembelajaran yang dikembangkan melalui penggunaan atau pembuatan boneka puppet dari aplikasi kain perca yang belum pernah di kembangkan di sekolah TKN Cimenyan. Melalui pelatihan ini diharapkan dapat menambah wawasan para pengajar terkait media pembelajaran Anak Usia Dini dan untuk meningkatkan kreativitas anak usia dini. Kegiatan pelatihan ini dilakukan dalam beberapa tahap, diantaranya: tahapan awal atau pengumpulan data mengenai situasi sekolah TKN Cimenyan, keadaan sekolah dan bagaimana kondisi media pembelajaran para siswa yang berada di TKN Cimenyan. Selanjutnya tim pengusul melakukan seminar sebagai bentuk pengenalan boneka puppet dan kain perca dan workshop atau pelatihan dengan target yang diharapkan para pengajar TKN Cimenyan mampu menghasilkan media pembelajaran baru, dan berkontribusi pada pengalian dan pengembangan pemanfaatan perca kain dengan tujuan mengurangi sampah kain.Kata kunci: boneka puppet, kain perca, media pembelajaran, anak usia dini